Kualitas Hidup Remaja di Kotamobagu Sulawesi Utara pada Masa Pandemi Coronavirus Disease 2019 - Irmawaty Buleno; Jeini Ester Nelwan; Joshua Runtuwene; Aaltje Ellen Manampiring; Gustaaf Ratag (STIKes Payung Negeri Pekanbaru, 2021)
Introduction: Quality of life is a measure to see an individual's health status comprehensively. Quality of life is assessed based on physical, psychological, social and environmental domains. Adolescents are one of the population that must be considered. The purpose of this study was to analyze the quality of life of adolescents in Kotamobagu, North Sulawesi during the Corona Virus Disease 2019 (Covid-19) pandemic. Method: This is a quantitative research. This research was conducted in Kotamobagu in October-November 2021. The respondents in this study were 441 teenagers who were junior high and high school students. The factors analyzed are the general quality of life of adolescents and the quality of life based on the dimensions of physical, psychological, social and environmental health. The data obtained were analyzed univariately. Results: The results of this study indicate that the quality of life of adolescents in Kotamobagu is more than 80% in the moderate and poor categories. The results of this study also showed that the average score of the quality of life for adolescents was 56.95. When viewed based on 4 dimensions of quality of life according to WHOQoL, namely physical, psychological, social and environmental health. The average score for the physical health dimension is 50.12, the psychological dimension is 60.89, the social relationship dimension is 51.32 and the environmental dimension is 64.89. Conclusion: That can be conclude that the quality of life of adolescents in Kotamobagu is still problematic, especially in the dimensions of physical health and social relations.